The Influence of Discussion-Based Learning Methods on Student Learning Outcomes Class XI in the Fruit Plant Agribusiness Subject at SMK N 1 Mamasa, Mamasa Regency - Sri Wahyu Tudang; Muhammad Rais; Nurmila Nurmila (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is classroom action research which aims to improve the learning outcomes of class XI students at ATPH SMKN 1 Mamasa. The independent variable in this research is a discussion-based learning method, while the dependent variable is the learning outcomes in the fruit crop agribusiness subject class XI ATPH Smkn 1 Mamasa. The population in this study were all students at SMKN 1 Mamasa, while the sample was 26 students, precisely in the ATPH class at SMKN 1 Mamasa. The research results show that discussion-based learning methods can improve student learning outcomes in fruit crop agribusiness subjects. In the first cycle the post-test average was 63.8%, while the second cycle post-test average was 80.7%. It can be concluded that the application of discussion-based learning methods can improve the learning outcomes of class XI ATPH SMKN 1 Mamasa students.